The Effect of FHRM and Open Innovation on Organizational Resilience mediated by Intellectual Capital on Employees of PT Telkom Indonesia in Jakarta - Putra, Jaka; Yusuf, M. Maulana; Fauziah, Vina; Emilisa, Netania (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the influence of Flexible Human Resource Management (FHRM) and open innovation on organizational resilience, mediated by intellectual capital. The research was conducted on employees of PT. Telkom Indonesia in Jakarta, using a quantitative method with a survey approach. Data were collected through questionnaires distributed to 181 respondents selected using a purposive sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) to examine both direct and mediating relationships among variables. The results reveal that FHRM and open innovation significantly impact organizational resilience, both directly and through the mediating role of intellectual capital. Intellectual capital was found to be a critical factor in strengthening the influence of FHRM and open innovation on organizational resilience. These findings provide practical implications for companies in designing human resource management and innovation strategies to enhance adaptability and organizational sustainability in the face of dynamic business environment challenges.